The Contribution of Patriarchy to the Concept of Manhood in African Societies: A Marxist Reading of Isidore Okpewho’s The Last Duty (Language Circle: Journal of Language and Literature, 2019)
This paper explores the concept of patriarchy as an undesirable ideology that promotes the oppression of the weak and vulnerable in society by the strong and powerful in Isidore Okpewho’s The Last Duty. It is widely held that patriarchy promotes the domination of men over women and promotes an artificial hierarchy of class in which women become subordinates to their male gender. Yet, patriarchy does not only make subjugates of women. Depending on the dictates and expectations of a culture, men, like women, can equally be made subjugates of patriarchy if they are deemed unworthy of the title of a man. This usually happens when they do not measure up to the standard of societal expectations, particularly, within African cultural setting. Using the theory of Marxism, this paper argues that patriarchy not only succeeds in creating a society that operates on classism in which women are the subordinates; men too become victims. In addition, patriarchy inflicts deep psychological trauma on men and women who suffer its tenets. The conclusion is that men and women collectively fight patriarchy in order to achieve an egalitarian society where synergy can be harnessed for the betterment of all.